2012
DOI: 10.1111/j.1601-183x.2011.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hippocampal gene expression by 7‐nitroindazole in rats submitted to forced swimming stress

Abstract: Nitric oxide (NO) is an atypical neurotransmitter that has been related to the pathophysiology of major depression disorder. Increased plasma NO levels have been reported in depressed and suicidal patients. Inhibition of neuronial nitric oxide synthase (nNOS), on the other hand, induces antidepressant effects in clinical and pre-clinical trials. The mechanisms responsible for the antidepressant-like effects of nNOS inhibitors, however, are not completely understood. In this study, genomic and proteomic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 78 publications
2
7
0
1
Order By: Relevance
“…NO has been involved in many signaling pathways related to stress and MDD, as well as to the antidepressant activity of classical drugs (Wegener et al, 2003;Joca & Guimarães, 2006;Wegener & Volke, 2010;Hiroaki-Sato et al, 2014). Corroborating the results from the present study, pharmacological inhibition of NOS induces antidepressant-like effects in the learned helplessness paradigm (Stanquini et al, 2017) and other models, such as forced swimming test (Ferreira et al, 2012;Montezuma et al, 2012;Sales et al, 2017) and unpredictable chronic stress (Yazir et al, 2012). Furthermore, activation and expression levels of NOS is attenuated by treatment with antidepressant drugs (Finkel et al, 1996;Wegener et al, 2003;Dhir & Kulkarni, 2007Zomkowski et al, 2010;Zhou et al, 2011;Bollinger et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…NO has been involved in many signaling pathways related to stress and MDD, as well as to the antidepressant activity of classical drugs (Wegener et al, 2003;Joca & Guimarães, 2006;Wegener & Volke, 2010;Hiroaki-Sato et al, 2014). Corroborating the results from the present study, pharmacological inhibition of NOS induces antidepressant-like effects in the learned helplessness paradigm (Stanquini et al, 2017) and other models, such as forced swimming test (Ferreira et al, 2012;Montezuma et al, 2012;Sales et al, 2017) and unpredictable chronic stress (Yazir et al, 2012). Furthermore, activation and expression levels of NOS is attenuated by treatment with antidepressant drugs (Finkel et al, 1996;Wegener et al, 2003;Dhir & Kulkarni, 2007Zomkowski et al, 2010;Zhou et al, 2011;Bollinger et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…The non-selective NOS inhibitor, l-N G -nitroarginine methyl ester (l-NAME), and the selective neuronal NOS inhibitor, 7-nitroindazole, induce dose-dependent antidepressant-like effects in the forced swimming test [7][8][9]. Furthermore, hippocampal NOS expression is significantly increased in depressed patients [10].…”
Section: Introductionmentioning
confidence: 98%
“…In depressed patients, hippocampal NOS expression is significantly increased [ 23 ]. Interestingly, it was found that the non-selective NOS inhibitor, L- N G -nitroarginine methyl ester (L-NAME), and the nNOS selective inhibitor 7-NI, induce dose-dependent antidepressant-like effects in the forced swimming test [ 24 , 25 , 26 ]. Another report showed that the clinical antidepressant Fluoxetine raises brain eNOS expression in the arginine depressive rat model [ 27 ].…”
Section: Resultsmentioning
confidence: 99%